Neutrophil function and bactericidal activity against Staphylococcus aureus after cardiac surgery with cardiopulmonary bypass. Issue 4 (23rd August 2021) - Lesouhaitier, Mathieu; Gregoire, Murielle; Gacouin, Arnaud; Coirier, Valentin; Frerou, Aurélien; Piau, Caroline; Cattoir, Vincent; Dumontet, Erwan; Revest, Matthieu; Tattevin, Pierre; Roisne, Antoine; Verhoye, Jean-Philippe; et al.
Abstract: Staphylococcus aureus is the main bacterial pathogen encountered in mediastinitis after cardiac surgical procedures; it remains a devastating complication with a high mortality rate. As neutrophils have a primordial role in the defense against staphylococcus infection and cardiopulmonary bypass (CPB) is known to induce immunosuppression, the aim of this study was to investigate CPB impact on neutrophil functions. Patients without known immunosuppression scheduled for cardiac surgery with CPB were included. Bone marrow and blood samples were harvested before, during, and after surgery. Neutrophil phenotypic maturation and functions (migration, adhesion, neutrophil extracellular trap [NET] release, reactive oxygen species (ROS) production, phagocytosis, and bacteria killing) were investigated. Two types of Staphylococcus aureus strains (one from asymptomatic nasal carriage and another from mediastinitis infected tissues) were used to assess in vitro bacterial direct impact on neutrophils. We found that CPB induced a systemic inflammation with an increase in circulating mature neutrophils after surgery. Bone marrow sample analysis did not reveal any modification of neutrophil maturation during CPB. Neutrophil lifespan was significantly increased and functions such as NET release and ROS production were enhanced after CPB whereas bacteria killing and phagocytosis were not impacted. Results were similar with the two different isolates of Staphylococcus aureus . These data suggest that CPB induces a recruitment of mature neutrophils via a demargination process rather than impacting their maturation in the bone marrow. In addition, neutrophils are fully efficient after CPB and do not contribute to postoperative immunosuppression. Graphical Abstract: Cardiopulmonary bypass does not immediately affect neutrophils functions.